2021
DOI: 10.1177/20451253211015070
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine re-challenge and initiation following neutropenia: a review and case series of 14 patients in a high-secure forensic hospital

Abstract: Objective: Clozapine remains the most effective intervention for treatment resistant schizophrenia; however, its use is prohibited following neutropenias. We review neutrophil biology as applied to clozapine and describe the strategies to initiate clozapine following neutropenia used in a case series of 14 consecutive patients rechallenged in a United Kingdom (UK) high-secure psychiatric hospital. We examine outcomes including the use of seclusion and transfer. Methods: A case series of 14 male patients with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 94 publications
(120 reference statements)
0
18
0
Order By: Relevance
“…Indeed, it has been shown that the majority of those on the UK non-rechallenge database can be safely re-prescribed clozapine 12 . A substantial fraction of apparent clozapine-related neutropenia (and even agranulocytosis) is actually a manifestation of benign neutropenia, in which successful rechallenge is possible 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that the majority of those on the UK non-rechallenge database can be safely re-prescribed clozapine 12 . A substantial fraction of apparent clozapine-related neutropenia (and even agranulocytosis) is actually a manifestation of benign neutropenia, in which successful rechallenge is possible 37 .…”
Section: Discussionmentioning
confidence: 99%
“… 238 Risk for CIN and CIA is estimated to be 3% and 0.4–0.7%, respectively. 217 , 287 Although CIN or CIA can occur at any time during treatment, 288 , 289 the highest incidence rates have been observed during the first 6–18 weeks of treatment (49% cases of neutropenia, 82% cases of agranulocytosis) with a clear subsequent risk decrease after six months. 73 , 213 , 217 , 287 , 290 This should be considered when a comorbid somatic disorder necessitates treatment with a drug also linked to blood dyscrasia.…”
Section: Side Effects Of Clozapinementioning
confidence: 99%
“…This procedure has reduced risk of death from CIA to less than 1 in 10.000 patients 150 . Risk for CIN and CIA is estimated to be 3 percent and 0.4-0.7 percent, respectively 151,152 . Although CIN or CIA can occur at any time during treatment 153,154 , the highest incidence rates have been observed during the first 6-18 weeks of treatment (49 percent cases of neutropenia, 82 percent cases of agranulocytosis) with a clear subsequent risk decrease after six months 72,151,152,155,156 .…”
Section: Hematological Side Effectsmentioning
confidence: 99%
“…Risk for CIN and CIA is estimated to be 3 percent and 0.4-0.7 percent, respectively 151,152 . Although CIN or CIA can occur at any time during treatment 153,154 , the highest incidence rates have been observed during the first 6-18 weeks of treatment (49 percent cases of neutropenia, 82 percent cases of agranulocytosis) with a clear subsequent risk decrease after six months 72,151,152,155,156 . This should be considered when a comorbid somatic disorder necessitates treatment with a drug also linked to blood dyscrasia.…”
Section: Hematological Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation